2024
DOI: 10.1021/acs.biomac.3c01183
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mucoadhesive Properties of Gelatin through Chemical Modification with Unsaturated Anhydrides

Elvira O. Shatabayeva,
Daulet B. Kaldybekov,
Leila Ulmanova
et al.

Abstract: Gelatin is a water-soluble natural polyampholyte with poor mucoadhesive properties. It has traditionally been used as a major ingredient in many pharmaceuticals, including soft and hard capsules, suppositories, tissue engineering, and regenerative medicine. The mucoadhesive properties of gelatin can be improved by modifying it through conjugation with specific adhesive unsaturated groups. In this study, gelatin was modified by reacting with crotonic, itaconic, and methacrylic anhydrides in varying molar ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…In an NMR spectroscopic study, they reported the disappearance of vinyl protons of polyethylene glycol diacrylate when mixed with mucin . Subsequently, our research group demonstrated a similar enhancement in the mucoadhesive properties of cationic, anionic, and neutral polymers upon the introduction of methacryloyl moieties . In our most recent study, we further showed that the mucoadhesive properties of gelatin could be significantly enhanced by modifying this biopolymer through reactions with crotonic, itaconic, and methacrylic anhydrides.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In an NMR spectroscopic study, they reported the disappearance of vinyl protons of polyethylene glycol diacrylate when mixed with mucin . Subsequently, our research group demonstrated a similar enhancement in the mucoadhesive properties of cationic, anionic, and neutral polymers upon the introduction of methacryloyl moieties . In our most recent study, we further showed that the mucoadhesive properties of gelatin could be significantly enhanced by modifying this biopolymer through reactions with crotonic, itaconic, and methacrylic anhydrides.…”
Section: Introductionmentioning
confidence: 54%
“…The strong adhesion of FITC-methacrylated L-PEI and crotonylated L-PEI can be attributed to the presence of unsaturated CC within these polymers, which could potentially form covalent bonds with thiol groups present on mucosal surfaces . The contribution of the amine groups within these polymers to adhesion will be minimal at pH to 7.4, since their macromolecules will be either noncharged or negatively charged.…”
Section: Resultsmentioning
confidence: 99%
“…The well-suited backbone of gelatin offers superb biocompatibility, biodegradability, and natural abundance that comes at meagre price. , Despite these advantages, gelatin lacks cohesion and interfacial adhesion strength, which could be tuned through modifications of surface functionalities . Physical mixing with tannic acid/PEG, photo-cross-linking with thiol/acrylate, cryo-polymerization, and reaction with transglutaminase are reportedly used to enhance adhesion and cohesion of gelatin. Chemical cross-linking with formaldehyde and glutaraldehyde in resorcinol has been found to enhance the bonding strength of gelatin-resorcin-formalin (GRF) and gelatin-resorcin-glutaraldehyde glues. , However, toxicological implications arise from the release of the aldehydes upon degradation of the bioadhesive.…”
Section: Introductionmentioning
confidence: 99%